A perfect murder [videorecording (DVD)] - Davis, Andrew, 1946-; Douglas, Michael, 1944-; Paltrow, Gwyneth, 1972-; Mortensen, Viggo, 1958-; Knott, Frederick (Distributed by Warner Home Video, 2009)
Steven Taylor, a rich commodities trader about to lose his fortune, is married to young, rich Emily, who is having an affair. In order to solve both of his problems, he plots to have his wife killed.